Control and autonomy: resource dependence relations and non-profit organizations. Issue 2 (12th April 2021) - Arvidson, Malin; Linde, Stig
Abstract : Purpose: For non-profit organizations (NPOs) external funding is an essential resource. Studies highlight how control is attributed to funders and so external funding threatens the autonomy of the recipient organization. The purpose of this study is to investigate how external control can be structured and exercised, and to explore how control interacts with organizational autonomy. Design/methodology/approach: The research is based on interviews and participant observations with NPOs and their funders over a period of time. It reports from four different funding-relations: contract-based, social investment, gift-funded and civil society–public partnership. The concept of organizational discretion is used to analyse how control and autonomy are interconnected in these relationship. Findings: The analysis illustrates the value in exposing the different discretionary boundaries related to external control and how control can become a sparring partner in the organization's striving for autonomy. A concluding argument is that control and autonomy are each other's companions rather than antagonists. The study leads us to question a general assumption that NPOs strive to avoid resource dependence and external control but instead may use such control to develop strategies for independence and self-realization. Originality/value: The empirical material is unique as it includes voices of recipient organizations and funders, and offers a comparison of different controlling-relations. The study presents an innovative analytical framework based on the concepts of discretionary space and reasoning, which supports a critical discussion regarding the idea of external control as detrimental to the autonomy of NPOs.